Viewing the choroid: where we stand, challenges and contradictions in diabetic retinopathy and diabetic macular oedema. Issue 5 (22nd August 2016) - Campos, António; Campos, Elisa J.; Martins, João; Ambrósio, António Francisco; Silva, Rufino
Abstract: Diabetic macular oedema (DMO) is the leading cause of vision loss in the working‐age population. Blood–retinal barrier (BRB) dysfunction in diabetic retinopathy (DR), mainly at the level of the retinal vessels, has long been related with leakage and fluid accumulation, leading to macular oedema. However, the nourishment of the macula is provided by the choroid and a diabetic choroidopathy has been described. Therefore, there has been a growing interest in studying the role of the choroid in the pathophysiology of DR and DMO, mainly by optical coherence tomography (OCT). Nevertheless, there are conflicting results in the different studies. We summarize the results from the available studies, describe the limitations and confounding factors and discuss future procedures to avoid bias.